Oxidative metabolism of typical phenolic compounds of Danshen by electrochemistry coupled to quadrupole time-of-flight tandem mass spectrometry. (15th June 2020) - Yang, Juan; Chen, Yan; Zhen, Xiao-Ting; Dong, Xin; Ye, Li-Hong; Zheng, Hui; Cao, Jun
Highlights: EC/Q-TOF/MS is a promising analytical tool in the prediction of metabolic transformations. EC/Q-TOF/MS was successfully applied to investigate five phenolic compounds in Danshen. The technology used for functional food has rarely been reported so far. This method was in good agreement with the experimental results in vitro and in vivo. Abstract: An electrochemistry coupled to online quadrupole time-of-flight tandem mass spectrometry (EC/Q-TOF/MS) was applied to investigate the oxidative transformation and metabolic pathway of five phenolic acids in Danshen sample. Simulation of the phase I oxidative metabolism was carried out in an electrochemical reactor equipped with a glassy carbon working electrode. The phase II reactivity of the generated oxidative products towards biomolecules (such as glutathione) was investigated by ways of covalent adduct formation experiments. The results obtained by EC/MS were compared with well-known in vitro studies by conducting rat liver microsome incubations. Structures of the electrochemically produced metabolites were identified by accurate mass measurement and previously results in vivo metabolites. It was indicated that the electrochemical oxidation was in good accordance with similar products found in vivo experiments. In conclusion, this work confirmed that EC/Q-TOF/MS was a promising analytical tool in the prediction of metabolic transformations of functional foods.